Geography,Historyand International Crafts Festival of Kokand City - Mashrabovich, ZhobborovA’zam; Azamzhon kizi, Tojiboeva Mahliyo; Ilknur, Akhmadjonov (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the geography and history of the city of Kokand, the international craft festival held for the first time in the Central Asian region, scientific and Scientific and popular information is given.